Mesenchymal stem cells generate pericytes to promote tumor recurrence via vasculogenesis after stereotactic body radiation therapy. Issue 2 (1st June 2016) - Wang, Huan-Huan; Cui, Yao-Li; Zaorsky, Nicholas G.; Lan, Jie; Deng, Lei; Zeng, Xian-Liang; Wu, Zhi-Qiang; Tao, Zhen; Guo, Wen-Hao; Wang, Qing-Xin; Zhao, Lu-Jun; Yuan, Zhi-Yong; et al.
Highlights: To determine the mechanisms behind SBRT stimulating MSC migration and differentiation. Bone-marrow derived MSCs migrate to the tumor parenchyma and differentiate into pericytes after SBRT, and promoting tumor recurrence. MSC migration and maturation may be abrogated with AMD3100 and imatinib. This novel treatment strategy warrants clinical investigation. Abstract: Background: Stereotactic body radiation therapy (SBRT) is postulated to enhance the recruitment of mesenchymal stem cells (MSCs) into the tumor microenvironment, which promote tumor recurrence. The aim of this study is to determine the molecular mechanisms behind SBRT stimulating MSC migration and differentiation. Methods: In vitro, mediated factors and migrated MSCs (post-SBRT) were generated. In vivo, bone-marrow derived MSCs were identified and harvested from green fluorescent protein (GFP)-expressing transgenic male mice and transplanted into sub-lethally irradiated recipient female mice to establish a model of bone marrow transplantation. Lewis lung carcinoma and malignant melanoma-bearing recipient mice were treated with SBRT, 14 Gy/1 fraction. The migration and differentiation potential of MSCs were characterized. Results: SBRT increased the release of stromal cell derived factor-1α (SDF-1α) and platelet-derived growth factor-B (PDGF-B) by tumor cells; these ligands bound to chemokine (C–X–C motif) receptor 4 (CXCR4) and platelet-derived growth factor receptor-β (PDGFR-β), respectively, on circulating bone marrow-derived MSCs, resulting in engraftment of the MSCs into the tumor parenchyma. The newly-homed MSCs differentiated into pericytes, which induced the tumor vasculogenesis, and promoted tumor regrowth. Targeted therapies, AMD3100 and imatinib abrogated MSC homing, vasculogenesis, and tumor regrowth. Conclusion: Bone-marrow derived MSCs migrate to the tumor parenchyma and differentiate into pericytes, inducing tumor vasculogenesis after SBRT, and promoting tumor recurrence. MSC migration and maturation may be abrogated with AMD3100 and imatinib. This novel treatment strategy warrants clinical investigation.